2018
DOI: 10.1002/lary.27355
|View full text |Cite
|
Sign up to set email alerts
|

Social isolation alters ultrasonic vocalizations but not thyroarytenoid neuromuscular junctions in old rats

Abstract: NA. Laryngoscope, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Wöhr et al found that male rats exposed to a brief period of social isolation produced more than twice the amount of USVs when compared to other rats, likely due to increased social motivation after isolating [ 5 ]. However, after longer periods of isolation (2–6 months), studies have found that socially isolated male rats produced fewer 50 kHz USVs with lower amplitude in response to a female rat than socially-housed rats [ 155 , 156 ]. Thus, it appears that while short-term social isolation may increase USV production rates in social situations, long-term social isolation decreases the number and amplitude of social USVs.…”
Section: Review Of Sex Differencesmentioning
confidence: 99%
“…Wöhr et al found that male rats exposed to a brief period of social isolation produced more than twice the amount of USVs when compared to other rats, likely due to increased social motivation after isolating [ 5 ]. However, after longer periods of isolation (2–6 months), studies have found that socially isolated male rats produced fewer 50 kHz USVs with lower amplitude in response to a female rat than socially-housed rats [ 155 , 156 ]. Thus, it appears that while short-term social isolation may increase USV production rates in social situations, long-term social isolation decreases the number and amplitude of social USVs.…”
Section: Review Of Sex Differencesmentioning
confidence: 99%
“…1 Observable deficits in SLN function are routinely encountered in the setting of age-related vocal atrophy, iatrogenic injury, vocal fold paralysis, neurodegenerative conditions, and laryngeal synkinesis. 2,3 The underlying pathophysiology of age-related, and neurodegenerative SLN dysfunction is not well understood. 4,5 Nerve conduction studies (NCS) are an important tool in the management and diagnosis of many peripheral nerve pathologies including spinal cord injury, brachial plexus injury, and carpal tunnel syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Injury to this nerve results in marked functional deficits including diminished laryngeal sensation and loss of pitch control and is associated with an increased frequency of dysphagia, aspiration, and altered voice 1 . Observable deficits in SLN function are routinely encountered in the setting of age‐related vocal atrophy, iatrogenic injury, vocal fold paralysis, neurodegenerative conditions, and laryngeal synkinesis 2,3 …”
Section: Introductionmentioning
confidence: 99%
“…Isolating the animals immediately post-weaning produces symptoms of depression (such as reduced reward anticipation) that do not resolve when the animals are reunited postadolescence (Shetty & Sadananda, 2017). Rats isolated while relatively young have been shown to make fewer Ultra-Sonic Vocalisations (USVs), or show aggressive behaviours towards other rats (Dakendar et al, 2009) and these effects continue into adulthood (Johnson, 2018). There appears to be conflicting evidence about whether anxious/depressive behaviours appear to increase when rats are isolated for a significant period of time.…”
Section: Animal Modelsmentioning
confidence: 99%